Assessing Pregnancy's Influence on Rectal and Corneal Temperature in Female Cats - Ozcan, Candemir; Safak, Tarik; Dellalbasi, Ayse Basak; Dogan, Elif (Wiley, 2025)
ABSTRACTObjectiveThis study aimed to investigate the effect of pregnancy status on corneal temperature (CT) and rectal temperature (RT) in female cats.Animals studiedFifteen pregnant and fifteen anoestrus cats were included in this study.ProceduresPregnant cats had gestation periods ranging from 20 to 45 days, and vaginal smears were taken to assess the oestrous cycles of anoestrus cats. CT was measured using a FLIR E90 thermal camera, while RT was measured with a digital thermometer. Statistical analysis was conducted to evaluate temperature differences between the two groups.ResultsAnoestrus cats (38.4 ± 0.55°C) had a significantly higher RT compared to pregnant cats (37.89 ± 0.58°C) (p = 0.02). The right (R) CT of anoestrus cats (36.58 ± 1.19°C) and pregnant cats (36.55 ± 1.41°C) did not differ statistically (p > 0.05). Similarly, no significant difference was observed in the left (L) CT between anoestrus cats (36.94 ± 0.96°C) and pregnant cats (36.18 ± 1.61°C) (p > 0.05). Furthermore, there was no statistical difference between the R‐CT and L‐CT of the groups (p > 0.05). A positive and linear correlation was found between RT and R‐CT in pregnant cats (r = 0.38, R2 = 0.14), with the regression equation y = ‐0.14x + 43.63.ConclusionThis study demonstrates that pregnancy status significantly affects RT but not CT in female cats. Specifically, pregnant cats exhibited statistically lower RT compared to those in anoestrus. However, despite this statistical significance, RT may not be a reliable clinical indicator of pregnancy in cats. RCT is preferable as it provides a stress‐free, consistent, and reliable alternative to RT measurement in pregnant cats. Further research is needed to explore more consistent markers for pregnancy status in felines.
Keywords: rectal temperature; Veterinary medicine; SF600-1100; Original Article; corneal temperature; pregnancy; thermal camera; feline